The importance of small hotels in tourism industry development - Angela Milenkovska Klimoska; Viktorija Trajkov (UTMS Journal of Economics, 2023)
The tourism industry is experiencing its greatest expansion since the time of Thomas Cook until today. Namely, the last 20 years have been a sign of dominant growth and development of tourism, in addition to the fact that at the same time, the world economy is under attack from economic crises. The continuous and high development of tourism is due primarily to the expansion of the hotel industry, seen through the parameters: investments in new hotel capacities, increasing the level of quality of services, and an offer that should satisfy the demands of the modern tourist. Dynamic development and the changes that it conditions dynamize the competition of tourist entities to keep up with the ever-increasing competition in the international tourist market. Discerning modern tourists, in addition to insisting on value for the price they pay, prefer programs of the type that provide "rest for the soul", which are distinguished by ecological, health, recreational and spiritual contents, healthy organic food, and warm hospitality from their hosts, which is called a kind of new tourist vision. At the same time, they expect their requirements to be fulfilled in full and with delivered value for money - value for many, but also hospitality and a kind of integration with their hosts, which is primarily possible in small hotels, which is why they can be called " small hotels" with a big soul".
Keywords: L83; M31; M12; 330; hotel; service; staff; quality; competition